The Increase of Flavonoids in Pericarpium Citri Reticulatae (PCR) Induced by Fungi Promotes the Increase of Antioxidant Activity. (2nd December 2018) - Wang, Fu; Chen, Lin; Li, Feng-qing; Liu, Su-juan; Chen, Hong-ping; Liu, You-ping
Abstract : There are thousands of traditional Chinese medicines in China, and they all have to be stored for a period of time for the reason of market price or other factors. But some traditional Chinese medicines especially need to be stored longer, and the clinical efficacy will be better. The cause and mechanism of this phenomenon have attracted much attention in recent years. In this study, we analyze the reason of "the longer storage period the better" of Pericarpium Citri Reticulatae (PCR); method of microscopic and molecular identification was used to identify the fungi separated and purified from PCR. The HPLC and UV spectrophotometry methods were used to determine the contents of flavonoids in PCR. The isolated fungi were inoculated into sterile samples to screen the fungi closely related to the change of flavonoids. The results indicate that the strain of Aspergillus niger could obviously promote the contents of flavonoids, and it could also increase the antioxidant effect of PCR. In conclusion, this study explains the reason of "the longer storage period the better" of PCR from the perspective of microbe, proving the beneficial effect of microorganism on the surface of PCR.